(untitled) (Ius Novum, 2023)
The article presents the issue of a misdemeanour of proposing to commit an unlawful act in order to obtain a material benefit classified in Article 142 MC. In order to provide full characteristics of the discussed type of misdemeanour, a classical pattern based on the traditional division of statutory features of the type of prohibited act has been adopted. The author discusses such issues as statutory penalties for this misdemeanour and concurrence of provisions. The article also draws special attention to issues raising doctrinal controversies, including inter alia: approach to the object of protection, the interpretation of the features of “prostitution”, “material benefit” or “other behavior violating public order”. A number of specific issues were also analysed, including liability under Art. 142 MC persons providing roadside sexual services.